A replication study of GWAS-genetic risk variants associated with Parkinson's disease in a Spanish population. (1st November 2019) - Tejera-Parrado, Cristina; Jesús, Silvia; Periñán, María Teresa; Buiza-Rueda, Dolores; Oliva-Ariza, Guillermo; Adarmes-Gómez, Astrid D; Macías-García, Daniel; Gómez-Garre, Pilar; Mir, Pablo
Highlights: We studied five polymorphisms previously associated to PD, in PD-patients and healthy controls. Only two loci ( ACMSD/TMEM163 and MAPT ) were related with the susceptibility to PD in our population. A suggestive association between ACMSD/TMEM163 and an increased risk of PD was found. A suggestive association between MAPT and a decreased risk of PD was found. Abstract: Recently, 5 previously Parkinson's disease (PD)-related loci: ACMSD/TMEM163, STK39, MIR4697, SREBF1/RAI1PD and MAPT, have been associated to PD in a Southern Spanish population. However, due to the small sample size of the cohort, this association did not reach genome wide significance. Our aim was to investigate the robustness of this association in a larger and independent cohort from the South of Spain. Variants were genotyped employing TaqMan SNP Genotyping Assay and high resolution melting analysis in 738 PD patients and 1138 healthy controls. Furthermore, a meta-analysis study was carried out with both cohorts. In the replication analysis, only two loci ( ACMSD/TMEM163 and MAPT ) were replicated with a Bonferroni significance level. In the meta-analysis study no loci reached a genome-wide significance level ( P <5xE-8), but a suggestive association ( P -value = 1.04E-6) between rs6430538 ( ACMSD/TMEM163 ) and an increased risk of PD was found. In addition, rs9468 ( MAPT ) was associated with a decreased risk of PD ( P -value = 5.70E-7). Our results add further support for the genetic involvement of these two loci in the susceptibility to PD in population from the South of Spain. We believe that our findings will be very useful for future genetic studies on PD.